Defending Your Reputation : A Practical Guide to Crisis Communications - Taylor, Simon (London : Thorogood Herndon : Stylus Publishing, LLC [Distributor], 2001)
Annotation If there's only one rule, it is that those organizations that have planned and prepared always do better than those which have done nothing.You almost certainly have detailed procedures in place for dealing with fire, theft, IT failure and so on. But do you have any sort of crisis contingency plan for protecting your reputation? Organizations, large and small, spend huge amounts of time and money on promoting their products, services and image. In today's world, a good name can be destroyed in a few hours.Simon Taylor, an expert in crisis management, explains the ways in which preparation and effective communication make all the difference in defending your reputation and placing it in the best possible position to recover. At a time when all organisations face public scrutiny to a far greater extent than ever before, this Report will help managers in all kinds of organizations, commercial, public and not for profit.
Trade